Decision Support System for Manufacturing Division Priority using AHP Method - Kencana, Christian (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2024)
In the competitive manufacturing landscape, especially in stamping and automobile parts production, optimizing production processes is a paramount challenge. This study addresses a manufacturing company's vulnerability to production reporting manipulation and inefficiencies in manual report generation. To tackle these challenges, we propose a vital system to combat the complexities and inaccuracies in existing reporting methods that significantly impede decision-making and operational efficiency. We introduce a novel, integrated system combining a production information system with an Analytical Hierarchy Process (AHP)-based decision support system. This hybrid solution aims to streamline report generation and boost decision-making within production divisions. The approach involves deploying a web-based system to simplify report creation and ensure accuracy and timeliness. The decision support system utilizes AHP to facilitate division prioritization, addressing critical issues promptly with data-driven insights. AHP's practicality and reliability assist in evaluating criteria for effective division prioritization. The implementation of this system marked significant improvements in production data management, evident from a substantial 68.17% user satisfaction rating. These results demonstrate the system's efficacy in enhancing decision-making, refining production processes, and boosting overall productivity. Furthermore, the system provides valuable insights into operator performance, fostering management recognition and appreciation, thus promoting transparency and accountability. The integration of an information system with AHP-based decision support emerges as a potent solution for manufacturing companies confronting similar challenges.